2021
DOI: 10.1155/2021/6692628
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inducible Nitric Oxide Synthase (iNOS) by Andrographolide and In Vitro Evaluation of Its Antiproliferative and Proapoptotic Effects on Cervical Cancer

Abstract: This work is aimed at investigating the expression levels of inducible nitric oxide synthase (iNOS) in cervical cancer and identifying a potential iNOS inhibitor. The data mining studies performed advocated iNOS to be a promising biomarker for cancer prognosis, as it is highly overexpressed in several malignant cancers. The elevated iNOS was found to be associated with poor survival and increased tumor aggressiveness in cervical cancer. Immunohistochemical and RT-PCR investigations of iNOS showed significant u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 70 publications
(68 reference statements)
0
13
0
1
Order By: Relevance
“…Given that the toxicity and side effects has been acknowledged with the vast majority of chemotherapeutic agents, in the past few decades, researchers have paid increasing attention to the anticancer investigation of natural active ingredients, especially andrographolide (Islam et al, 2018; Malik et al, 2021; Soo et al, 2019). Published projects have validated the multiple anticancer effects, such as its ability to colon cancer (Banerjee et al, 2021; Vukmirovic, Vo, Seymour, Rollo, & Mothersill, 2021), lung cancer (Luo et al, 2021), cervical cancer (Pasha et al, 2021), breast cancer (Wanandi et al, 2020), hepatoma cancer (Shi, Zhang, Zheng, Lu, & Ji, 2017) as well as renal carcinoma (Bi et al, 2020) and so on, which the cytotoxic effects on these cancer cells above were bound up with inhibiting proliferation (Khan, Mahfooz, & Ansari, 2020), migration and invasion (Pearngam, Kumkate, Okada, & Janvilisri, 2019), blocking cell cycle (Khan, Mahfooz, Faisal, Alatar, & Ansari, 2020), inducing apoptosis (Wang et al, 2020), restraining tumor angiogenesis (Kajal et al, 2019), as well as enhancing chemosensitivity (Li et al, 2020; Mao, He, Wang, Wu, & Wei, 2019). The main anticancer mechanisms of andrographolide are depicted in Figure 4.…”
Section: Pharmacologymentioning
confidence: 99%
“…Given that the toxicity and side effects has been acknowledged with the vast majority of chemotherapeutic agents, in the past few decades, researchers have paid increasing attention to the anticancer investigation of natural active ingredients, especially andrographolide (Islam et al, 2018; Malik et al, 2021; Soo et al, 2019). Published projects have validated the multiple anticancer effects, such as its ability to colon cancer (Banerjee et al, 2021; Vukmirovic, Vo, Seymour, Rollo, & Mothersill, 2021), lung cancer (Luo et al, 2021), cervical cancer (Pasha et al, 2021), breast cancer (Wanandi et al, 2020), hepatoma cancer (Shi, Zhang, Zheng, Lu, & Ji, 2017) as well as renal carcinoma (Bi et al, 2020) and so on, which the cytotoxic effects on these cancer cells above were bound up with inhibiting proliferation (Khan, Mahfooz, & Ansari, 2020), migration and invasion (Pearngam, Kumkate, Okada, & Janvilisri, 2019), blocking cell cycle (Khan, Mahfooz, Faisal, Alatar, & Ansari, 2020), inducing apoptosis (Wang et al, 2020), restraining tumor angiogenesis (Kajal et al, 2019), as well as enhancing chemosensitivity (Li et al, 2020; Mao, He, Wang, Wu, & Wei, 2019). The main anticancer mechanisms of andrographolide are depicted in Figure 4.…”
Section: Pharmacologymentioning
confidence: 99%
“…UV visible spectroscopic, melting temperature, and molecular fluorescent studies confirmed that annonalide interacts with CT DNA through intercalation with a stoichiometric ratio of 1:1. Docking study revealed that diterpene and DNA interact through van der Waals interaction [112]. Multiple interaction studies have been performed using different spectroscopic techniques and computational tools to extract the therapeutic value of andrographolide [113,114].…”
Section: Interaction Studiesmentioning
confidence: 99%
“…254 Andrographolide could also inhibit cervical cancer cell proliferation and promote apoptosis via decreasing inducible nitric oxide synthase (iNOS). 255 Beyond the above non-solid tumors, According to Loh et al, andrographolide inhibited cell survival and migration in human cervical cancer cells. This study showed therapeutic effects in treating cervical cancer may occur in andrographolide.…”
Section: Other Cancersmentioning
confidence: 99%
“…Parthenolide and andrographolide, according to Gunn et al, have anticancer stem cell action in multiple myeloma stem cells 254 . Andrographolide could also inhibit cervical cancer cell proliferation and promote apoptosis via decreasing inducible nitric oxide synthase (iNOS) 255 . Beyond the above non‐solid tumors, According to Loh et al, andrographolide inhibited cell survival and migration in human cervical cancer cells.…”
Section: Andrographolide In Cancersmentioning
confidence: 99%